Rancang Bangun Alat Flushing Biosolar B35 Menggunakan Filter Sedimen - Sigit Wahyudin; Kashadi Kashadi; Puji Basuki; Agustien Zulaidah; Candra Wahyu S; January Jefry P (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
Biosolar is a vegetable oil obtained from palm oil or Crude Palm Oil. Biodiesel has combustion properties similar to petroleum diesel, and can replace it in various applications. However, it is more often used as an additive to diesel fuel. So far, the most common problem that often occurs among B35 biodiesel users is that the filter is clogged with a layer of scale from sedimentation that occurs in the fuel tank. The purpose of making a flushing tool is to help and facilitate the process of draining the fuel tank so that it can reduce the number of fuel filter replacements on vehicles. The method are observation, concept creation, design and continued with design drawings. Next is the material procurement and manufacturing process. The result obtained is a flushing tool with dimensions of 1,350cm x 400cm x 460cm. Test results on a maximum tank capacity 200 litters in 30 minutes.  Cost of materials and spare parts Rp. 9,793,000.